Observations of plasma blobs by OI 630 nm using ASI and photometer over Kolhapur, India - Nade, D. P.; Sharma, A. K.; Nikte, S. S.; Chavan, G. A.; Ghodpage, R. N.; Patil, P. T.; Gurubaran, S. (My University, 2014)
This paper presents observations of plasma blobs by nightglow OI 630.0 nm emissions using ground-based techniques, all sky imager and photometer from Kolhapur. The nightglow observations have been made at low latitude station, Kolhapur (16.42°N, 74.2°E, and 10.6°N dip lat.) during clear moonless nights for period of October 2011–April 2012. Generally, these occur 3 h after sunset (18:00 IST). Herein we have calculated velocities of plasma blobs using scanning method, introduced by Pimenta et al. (Adv Space Res 27:1219–1224, 2001). The average zonal drift velocity (eastward) of the plasma blobs were found to be 133 ms−1 and vary between 100 and 200 ms−1. The width (east–west expansion) and length (north–south expansion) of plasma blobs is calculated by recently developed method of Sharma et al. (Curr Sci 106(08):1085–1093, 2014b). Their mean width and length were in the range of 70–180 and 500–950 km respectively. The study shows that localized eastward polarization electric field plays an important role in the generation of plasma blobs.
Keywords: Plasma blobs; Plasma bubbles; All sky imager; OI 630.0 nm emission; Nightglow; Photometer; Kolhapur